Maternal and Fetal Outcome on Pregnancy in Advanced Maternal Age - Dewi, Sianty; Ferry, Ferry; Toynbee, Eddy; Prayudhana, Sandhy (Indonesian Socety of Obstetrics and Gynecology, 2016)
Objective: Pregnancy in advanced maternal age (AMA) was classified as high risk. The study aims to provide a better description of pregnancy outcome in AMA. Method: The cross sectional study was to review the demography, medical and obstetrics problems, mode of delivery, maternal and fetal outcome in Tangerang General Hospital as a referral center in Banten. The data were taken from medical records of 35-year-old and above women age who delivered on the period of January to December 2014. Result: The total number of delivery and live birth was 6,107 and 5,926 respectively, including 1,548 (25.36%) pregnancies in AMA. The prevalence of grandmultiparities was 11.4%. The average education level was mostly elementary. The prevalence of hypertension in pregnancy was 34.6%. There was increasing trend of miscarriages from 10.8% in 35-40-year-old group to 25% in above 45- year-old group. Pregnancy complications were higher consisting of 3.2% multifetal, 16.6% malpresentation, and 7.1% placenta previa. Cesarean section rate was 33.6%. Maternal near-missed cases were 56 of 1000 and the maternal mortality rate (MMR) was 932 of 100,000 live births. The prevalence of stillbirth and perinatal mortality were 5.3% and 12.9%; respectively. Conclusion: Adverse maternal and fetal outcome were higher in AMA as it takes special attention and multidiscipline-approached care started from preconception, antenatal, preparation of delivery, and also postpartum care. Keywords: advanced maternal age (AMA), fetal outcome, maternal outcome, pregnancy